Telomeres and their Role in Aging and Longevity - P. Tzanetakou, Irene; Nzietchueng, Rosine; N. Perrea, Despina; Benetos, Athanase (Current Vascular Pharmacology, 2014)
Telomeres are DNA-protein structures that form protective caps at the end of eukaryotic chromosomes. They constitute the safeguards of chromosome degradation and are responsible for maintaining genomic integrity. The multifactorial nature of telomere length (TL) regulation increases the perplexity of studies in the field. TL is characterized by a high variability among individuals (birth and later life) and among species but it is unknown whether this is associated with their lifespan potential. TL is also highly heritable, longer in women than in men; it is highly variable between tissues and organs and inversely related to chronological age. Accelerated telomere loss has been associated with many chronic diseases of aging. Premature aging or cellular senescence, seen in early life, through increased oxidative stress and DNA damage to telomeric ends may be initiators of processes related to these diseases. During the recent decade, research around telomere biology has rapidly expanded due to its dynamic involvement in aging and longevity. However, longevity is not necessarily an indication of disability-free aging. There is substantial scientific disagreement and controversial results, regarding even the basic nature of aging and the path to longevity. We review the current evidence linking telomere biology to aging processes and mechanisms leading to longevity.
Keywords: telomerase